2014
DOI: 10.3324/haematol.2014.103655
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric assessment to predict survival in older allogeneic hematopoietic cell transplantation recipients

Abstract: ABSTRACTpreviously described. 17 We selected a threshold age of 50 years because the optimal age for GA in this population has not been studied and this was the age at which reduction in transplant regimen intensity may be justified.18 A trained research assistant or nurse carried out the GA within one month prior to initiation of transplant conditioning. Occasionally, GA occurred 1-2 days after conditioning began. The treating physician determined suitability to undergo HCT and appropriate HCT treatment plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
163
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(179 citation statements)
references
References 36 publications
11
163
5
Order By: Relevance
“…13 The ability to perform tasks necessary to live independently in the community, that is, shopping, food preparation, housekeeping, laundry, transportation, handling finances and medication bears most importantly on the survival of older adults. Muffly et al 15 found that the presence of slow walking speed and low mental health before transplant also have prognostic value for poorer survival. Finally, older age and GvHD are principal risk factors for non-relapse death and late death; and even when alloHCT is successful, life expectancy is still lower than expected.…”
Section: Functional Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The ability to perform tasks necessary to live independently in the community, that is, shopping, food preparation, housekeeping, laundry, transportation, handling finances and medication bears most importantly on the survival of older adults. Muffly et al 15 found that the presence of slow walking speed and low mental health before transplant also have prognostic value for poorer survival. Finally, older age and GvHD are principal risk factors for non-relapse death and late death; and even when alloHCT is successful, life expectancy is still lower than expected.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Although age is a factor, research has shown that co-morbidities and performance status are stronger predictors of survival than age. [13][14][15][16] Wedding et al found that impairment of instrumental activities of daily living was the single most predictive variable of survival in their sample of AML patients ages 19-85 years (median 61.1). 13 The ability to perform tasks necessary to live independently in the community, that is, shopping, food preparation, housekeeping, laundry, transportation, handling finances and medication bears most importantly on the survival of older adults.…”
Section: Functional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that risk factors predictive of induction outcomes are also predictive of outcomes after BM transplantation, 44 further highlighting the need for systematic approaches to patient assessment in trials and practice. Ultimately, understanding specific patient vulnerabilities will help to: (1) predict treatment tolerance and benefit for available therapies, (2) inform novel clinical trial design to target specific patient subgroups and explore the relationship between tumor and patient biology, and (3) identify targets for intervention to improve supportive care during therapy (ie, exercise for physical impairment 45 ).…”
Section: Next Steps To Move Research To Practicementioning
confidence: 99%
“…However, we know that comorbidity, functional status and standard geriatric measures will stratify outcomes for older transplant patients. 10,11 Likewise, psychosocial health not only plays an important role as a prognostic factor, but psychosocial changes after transplant also influence post-transplant quality of life. Prospective studies are needed though, as morbidity and mortality classified as transplant-related may also be a consequence of pre-existing health conditions, especially for older adults being followed for 2-5 years after HCT.…”
mentioning
confidence: 99%